2005
DOI: 10.1158/0008-5472.can-05-1318
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPase-Activating Protein Deleted in Liver Cancer Suppresses Cell Proliferation and Invasion in Hepatocellular Carcinoma

Abstract: Deleted in liver cancer (DLC1) is a candidate tumor suppressor gene recently isolated from human hepatocellular carcinoma. Structurally, DLC1 protein contains a conserved GTPase-activating protein for Rho family protein (RhoGAP) domain, which has been thought to regulate the activity of Rho family proteins. Previous studies indicated that DLC1 was frequently inactivated in cancer cells. In the present study, we aimed to characterize the tumor suppressor roles of DLC1 in hepatocellular carcinoma. We showed that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
204
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 174 publications
(213 citation statements)
references
References 38 publications
9
204
0
Order By: Relevance
“…For instance, DLC1 (deleted in liver cancer), a GAP for Rho proteins, suppresses cell proliferation, migration and invasion in hepatocellular carcinoma cells. DLC1 is thought to serve as a tumor suppressor protein by antagonizing the oncogenic activity of Rho proteins in liver cancer (Wong et al, 2005;Xue et al, 2008). In contrast, p190A RhoGAP-deficient fibroblasts showed a defect in polarized cell migration (Tomar et al, 2009) although they did not exhibit any obvious defects in adhesion on extracellular matrix (Jiang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, DLC1 (deleted in liver cancer), a GAP for Rho proteins, suppresses cell proliferation, migration and invasion in hepatocellular carcinoma cells. DLC1 is thought to serve as a tumor suppressor protein by antagonizing the oncogenic activity of Rho proteins in liver cancer (Wong et al, 2005;Xue et al, 2008). In contrast, p190A RhoGAP-deficient fibroblasts showed a defect in polarized cell migration (Tomar et al, 2009) although they did not exhibit any obvious defects in adhesion on extracellular matrix (Jiang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DLC1 is emerging as a bona fide tumor suppressor gene, given that ectopic expression of DLC-1 in several common types human cancer cells that do not express the endogenous gene inhibits cell proliferation and induces caspase-3-mediated apoptosis in vitro as well as abolishes or reduces tumorigenicity in vivo [2,3,4,5,6,7,8]. Limited information is available on factors that regulate transcription of endogenous DLC1, however.…”
Section: Introductionmentioning
confidence: 99%
“…However, the activation of Rho proteins contributes to tumorigenesis and metastasis in many cancers 10 , and RhoGAP activity has a predominant role in the tumour suppressor functions of DLC1 11 . In different cell line models, ectopic expression of the RhoGAP mutant of DLC1 fails to suppress cell growth and motility 12,13 , and functional studies have shown that RhoGAP and the growth inhibitory activities of DLC1 are impaired as a result of T301K and S308I mutations, which were identified in prostate and colon cancer patients 14 . These studies suggest that RhoGAP activity and growth suppression activity are tightly associated.…”
mentioning
confidence: 99%